Metal-free approach towards efficient synthesis of FDCA using a p-toluene sulfonic acid (p-TSA)-derived heterogeneous solid acid catalyst and oxone over two steps from HMF, fructose and glucose - Tamboli, Asma T. Biradar; Kirdant, Swapnali P.; Jadhav, Vrushali H. (New Journal of Chemistry, 2022)
In this work, a metal-free approach towards the synthesis of 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethylfurfural (HMF), fructose and glucose is reported over two steps using a p-toluene sulfonic acid (p-TSA)-derived heterogeneous solid acid catalyst (p-TSA-POM) in the first step and oxone as an oxidant in the second step. HMF, fructose and glucose were converted to 2,5-diformylfuran (DFF) using the p-TSA-POM catalyst followed by oxidation of DFF to FDCA using oxone. To the best of our knowledge, this is the first metal-free approach for the synthesis of FDCA directly from glucose. DFF was obtained from HMF in 91% yield, whereas it was obtained in 85% and 61% yields from fructose & glucose, respectively. DFF was further converted to FDCA using oxone as an oxidant. FDCA was obtained in an overall yield of 84%, 78% and 56% from HMF, fructose & glucose, respectively.

Recent developments in the applications of biomass-derived sulfonated carbonaceous solid acid catalysts - Kirdant, Swapnali P.; Tamboli, Asma T. Biradar; Jadhav, Vrushali H. (Helvetica Chimica Acta, 2022)
Recently, carbon-based materials are gaining a lot of attraction. It is considered as an emerging area of research and has gained significant importance as an efficient catalyst/material in various fields. Biomass is abundantly available, cheap and a renewable carbon resource. Sulfonated carbonaceous solid acid catalyst can be derived by sulfonation of various sources of biomass such as sugars, lignin, fruit waste, agro-waste, bio-char, etc. Sulfonated carbonaceous solid acid catalysts can be used as a substitute to liquid acids. These catalysts possess a stable carbon skeleton and are insoluble in almost all organic solvents as well as under acidic/basic conditions. This review covers details about biomass-derived sulfonated carbonaceous solid acid catalysts and its catalytic activities in many important transformations such as hydrolysis of cellulose, synthesis of biodiesel, synthesis of various important chemicals and for various organic transformations.
Keywords: Biodiesel; Biomass; cellulose; Hydrolysis; sulfonated carbonaceous solid acid catalyst